Pedagogy of the oppressed body as a way to child's body literacy - Correia, Mesaque Silva (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
Freire's pedagogical thinking has significantly favored the expansion of formal and non-formal educational practices, and has contributed to the expansion of critical readings of the world in which educators have sought in their epistemological base support for their concerns. Thus, starting from the readings of the Freirean legacy, the objective of the present study is to conjecture possibilities, and not a rule to be followed, to anchor Physical Education teaching in the context of Early Childhood Education in the theoretical and methodological principles of “Pedagogy of the Oppressed Body. To this end, it presents and reflects on the guiding principles of such a proposal, in order to contribute to the debate in the field of Education and Physical Education around the importance of understanding the child as an existentially corporal being and as such does not learn and nor gain awareness with the mind alone.